(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the effectiveness of 38% hydrogen peroxide in teeth whitening with orthodontic appliances. Materials and methods: Forty specimens were made in the form of a bovine enamel/dentin block (9mm x 2mm), with 1mm of enamel and 1mm of dentin, were obtained. After embedding the specimen in acrylic resin, they were divided into 4 groups (n=10): Group 1: Negative Control, the specimen did not receive any treatment; Group 2: Only orthodontic brackets were bonded, without bleaching; Group 3: Orthodontic brackets and PH38%; Group 4: Positive control, submitted to bleaching treatment with PH38%, without brackets. The bleaching agent was applied once a week for 45 minutes for 4 weeks. The color was measured before placing the brackets and 7 days after bleaching using the L*a*b* coordinates of the CIE-Lab system, with a spectrophotometer. ΔE values ​​were statistically analyzed by ANOVA and Games-Howell tests (p<0.05). As for the L* and a* coordinates, the ANOVA, Student’s T, and Games-Howell post hoc tests were used (p<0.05); in the b* coordinate, ANOVA, Student’s T and Tukey’s post hoc tests were performed (p<0.05). Results: In ΔE, groups G3 and G4 were statistically like each other. In relation to the coordinates of L* and b*, the groups G3 and G4 presented different values ​​from each other, with G4 showing the highest averages; on the other hand, the a* coordinate presented the highest values ​​for G3. Conclusion: bleaching with PH38% was effective in teeth with orthodontic appliances.